Training for Assembly of Appropriate Technology-Based Battery Packs to Improve Vocational School Students' Competence in Supporting Green Energy Programs - Fachry Fathan Irsyad; I Gede Putu Oka Indra Wijaya; Ahmad Fahmi Aldarwis; Aminah Indahsari Marsuki; Jangkung Raharjo (CogniSpectra Publishing, 2026)
Background: Human resources skilled in energy storage technology, particularly lithium-ion batteries, are needed to support the increased use of electric vehicles in Indonesia. However, the material at the vocational school level is still far from green industry standards. The objective of this community service program is to improve the practical skills of students at SMKN 4 Bandung by providing training on battery manufacturing based on Appropriate Technology (TTG). Contribution: This activity truly benefits the school community by providing infrastructure that supports practice and improves project-based curricula. In addition, the program helps students independently produce core components for electric vehicles, supporting national energy independence. Method: The program implementation method consists of four main stages. First, conducting literature research and surveys on the necessary information; providing theory on battery management systems, also known as BMS; hands-on practice building a 36V 6Ah battery using a spot welder; and finally, conducting a comprehensive evaluation. Results: The results of the activity showed a significant increase in participants' knowledge; the average competency score increased from 59% in the pre-test to 85% in the post-test, and the satisfaction survey showed that the level of participants' appreciation of the relevance of the training reached 85.32%. Conclusion: The program successfully achieved its goal of reducing skill disparities among students. The results produced a prototype battery that can be installed on electric bicycles, proving that action-based learning is an effective method for incorporating renewable energy technology into vocational education environments.